2017
DOI: 10.1038/srep40314
|View full text |Cite
|
Sign up to set email alerts
|

Quantum dynamics study of energy requirement on reactivity for the HBr + OH reaction with a negative-energy barrier

Abstract: A time-dependent, quantum reaction dynamics approach in full dimensional, six degrees of freedom was carried out to study the energy requirement on reactivity for the HBr + OH reaction with an early, negative energy barrier. The calculation shows both the HBr and OH vibrational excitations enhance the reactivity. However, even this reaction has a negative energy barrier, the calculation shows not all forms of energy are equally effective in promoting the reactivity. On the basis of equal amount of total energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 49 publications
(101 reference statements)
0
4
0
Order By: Relevance
“…Additionally, full-dimensional quantum dynamics calculations of rate constants employing the J-shifting approximation are only available for a few polyatomic reactions. [21][22][23][24][25][26][27] a) Electronic mail: ralph.welsch@desy.de Most accurate thermal rate constant calculations for polyatomic molecules employ the quantum transition state concept [28][29][30][31][32][33][34][35] and the multi-configurational time-dependent Hartree (MCTDH) approach. 36,37 The quantum transition state concept has been proven as the most efficient method to treat the reaction dynamics of polyatomic systems rigorously.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, full-dimensional quantum dynamics calculations of rate constants employing the J-shifting approximation are only available for a few polyatomic reactions. [21][22][23][24][25][26][27] a) Electronic mail: ralph.welsch@desy.de Most accurate thermal rate constant calculations for polyatomic molecules employ the quantum transition state concept [28][29][30][31][32][33][34][35] and the multi-configurational time-dependent Hartree (MCTDH) approach. 36,37 The quantum transition state concept has been proven as the most efficient method to treat the reaction dynamics of polyatomic systems rigorously.…”
Section: Introductionmentioning
confidence: 99%
“…All the available temperature-dependent measurements of k 1 are shown in Figure in line with some other theoretical calculations and evaluations of the rate constant covering high temperatures. QST calculations of de Oliveira-Filho et al and quantum dynamics study by Wang et al, both on a full-dimensional ab initio potential energy surface, reporting inverse temperature dependence of k 1 at low temperatures, are unfortunately limited to 500 K and do not provide information on the behavior of k 1 at higher temperatures. In the work of Burgess et al, reporting a detailed chemical kinetic mechanism of the flame inhibition by the fire-suppressant 2-bromo-3,3,3-trifluoropropene, the following expression for the rate constant of reaction , k 1 = 3.4 × 10 –13 T 0.58 exp­(168/ T ) cm 3 molecule –1 s –1 , was proposed for use at flame temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…Reaction is also important in combustion chemistry, being an important step in flame inhibition mechanisms when using bromine-containing compounds as flame retardants. Another potential implication of the reaction at high temperatures is its involvement in the hot near-source volcanic plume chemistry . Surprisingly, despite the potential practical interest in the reaction at high temperatures, there are no experimental data for the reaction rate constant at temperatures higher than 460 K. Recent theoretical work on the OH + HBr reaction was also mainly focused on temperatures below 500 K, and only a few evaluations and theoretical efforts , have been undertaken to define the reaction rate constant at elevated temperatures. Although all these works predict a similar weak positive temperature dependence of k 1 at T > 500 K, the absolute values of k 1 differ by more than a factor of 2.…”
Section: Introductionmentioning
confidence: 99%
“…For reaction R1 , diverging cross sections at decreasing collision energy have been observed in recent quasiclassical trajectory and reduced-dimensional quantum dynamical calculations. 25 For reaction R2 , de Oliveira et al 23 reported excitation functions that seem to show extremely fast divergence of the reaction cross sections when the collision energy decreases, which was supported by the quantum dynamical calculations of D. Wang et al 26 The cross sections observed in molecular beam experiments by Kasai and co-workers 27 , 28 also increase with decreasing collision energy. For reactions with an early barrier, such as reactions R1 and R2 , Polanyi rules of reaction dynamics 29 predict that vibrational excitation of the reactants promotes the reaction less efficiently than an equal amount of translational energy.…”
Section: Introductionmentioning
confidence: 85%